PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSANDALAM MENENTUKAN KENDARAAN YANG LAYAK BEROPERASI (Studi Kasus: PT. Yasunli Abadi Utama Plastik) - Hernalom Sitorus; Rachmah Nursafitri (JURNAL SATYA INFORMATIKA, 2019)
Vehicle testing is a series of inspection of vehicle components that must meet the roadworthiness threshold requirements, to ensure the vehicles to be operated on the road are in good technical condition in order to maintain safety and smoothness in the process of sending goods to the customer. However, currently vehicles that are operated often experience obstacles such as strikes in the middle of the road, broken tires, hit by a ticket because the vehicle documents are not renewed so there is a delay in delivery that will harm the customer and the company itself. The problem with the company is that there is no specific method used by the mechanics and the head pool to find out which vehicles are feasible to operate. In this study using the Simple Additive Weighting (SAW) method to find optimal alternatives from a number of alternatives with certain criteria. This study will rank vehicles that are roadworthy, based on criteria such as vehicle year, completeness of letter, completeness of supporting accessories, periodic service period. The results of this study were obtained the value of the weight of a vehicle that is most feasible to operate.